1993
DOI: 10.1002/path.1711710305
|View full text |Cite
|
Sign up to set email alerts
|

Expression of keratin mRNAS and proteins in normal salivary epithelia and pleomorphic adenomas

Abstract: Control of keratin (K) gene expression may be important for cell differentiation in complex epithelia such as salivary gland. To investigate differences in distribution between keratin mRNAs and their respective proteins, a combined in situ hybridization (ISH) and immunohistochemical study was undertaken on nine normal salivary glands and seven pleomorphic adenomas. ISH employed riboprobes to K7, K8, K14, K18, and K19. Immunohistochemistry was performed on adjacent sections using monoclonal antibodies (MAbs) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 20 publications
2
21
0
2
Order By: Relevance
“…Although the enhanced immunolocalizations for CK16 in CIS cases corresponded to their definite mRNA levels, the loss of K13 immunopositivities seemed to be partly due to lowered K13 gene expression levels and partly due to unknown posttranslational events. Areas with gene expressions for such keratin subtypes as K1, K6, K7, K8, and K10 have been reported to be wider than their protein ones in normal oral mucosa and salivary glands, 25,26 salivary pleomorphic adenoma, 25 oral epithelial, 26 or epidermal 27 lesions. The tendencies were considered to be possible because the transcript forms might not always be translated to proteins due to some posttranscriptional regulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the enhanced immunolocalizations for CK16 in CIS cases corresponded to their definite mRNA levels, the loss of K13 immunopositivities seemed to be partly due to lowered K13 gene expression levels and partly due to unknown posttranslational events. Areas with gene expressions for such keratin subtypes as K1, K6, K7, K8, and K10 have been reported to be wider than their protein ones in normal oral mucosa and salivary glands, 25,26 salivary pleomorphic adenoma, 25 oral epithelial, 26 or epidermal 27 lesions. The tendencies were considered to be possible because the transcript forms might not always be translated to proteins due to some posttranscriptional regulations.…”
Section: Discussionmentioning
confidence: 99%
“…The tendencies were considered to be possible because the transcript forms might not always be translated to proteins due to some posttranscriptional regulations. 21,[25][26][27] In human skin epidermis, multiple microRNAs are thought to regulate gene expression of keratins during keratinocyte differentiation in vitro and in vivo. 28 Therefore, it is speculated that microRNA-induced repression of the K13 gene translation might occur as posttranscriptional regulation in the oral keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Although several investigators have examined the expression of CKs in neoplastic lesions of salivary glands, 19,[21][22][23][24][25][26][27][28][29][30][31] to the best of our knowledge this is the first time that the combined CK7 and CK20 profile of malignant salivary gland tumors is analyzed in a sizeable group of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have shown that different CKs are localized in the various compartments of normal salivary glands, for example, CK8 and CK18 are expressed in the luminal duct and acinar cells, while CK5 and CK14 are primarily seen in basal duct cells and myoepithelial cells. [21][22][23][24] Interestingly, CK7 has been shown to be expressed to a different degree in the various epithelial salivary gland elements; more specifically, the luminal cells of the salivary ducts are strongly positive for CK7, while the acinar, basal, and myoepithelial cells stain with less intensity or, according to some investigators, not at all. [21][22][23][24] On the other hand, CK20 has been reported to be consistently absent from all salivary gland epithelial elements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation